2020
DOI: 10.1155/2020/8978041
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Separation and Use of and Unmet Need for Contraception in Nepal: Results Based on a 2016 Survey

Abstract: Nepal is facing a large-scale labour migration—both internal and international—driven by economic and employment opportunities. There is sparse literature available at the national level which examines the link between migration and contraceptive use. This study aimed at identifying contraceptive use and the unmet need for family planning (FP) and exploring its correlates among the married women of reproductive age (MWRA) by their husbands’ residence status, using data from Nepal Demographic Health Survey 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The DSFMCs among Muslims was reduced by 42% compared with Orthodox Christians. This is supported by studies in Zambia,35 Ghana,37 38 Tanzania,39 Nigeria40 and rural Nepal 41 42. The findings show that the governments of the countries need to consider addressing different social determinants such as engagement of religious leaders; pieces of evidence have shown that those women who get FP-related massages from religious leaders have a high uptake of FP services 40.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The DSFMCs among Muslims was reduced by 42% compared with Orthodox Christians. This is supported by studies in Zambia,35 Ghana,37 38 Tanzania,39 Nigeria40 and rural Nepal 41 42. The findings show that the governments of the countries need to consider addressing different social determinants such as engagement of religious leaders; pieces of evidence have shown that those women who get FP-related massages from religious leaders have a high uptake of FP services 40.…”
Section: Discussionmentioning
confidence: 80%
“…This study demonstrated that demand satisfaction among women whose husbands were living elsewhere distant from them was reduced by 58% than those living together. This is complemented by studies in Nepal 42 43. Those women whose husbands lived elsewhere apart from them may have less often sexual contact.…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that could have played a role in low mCPR is male out-migration. A great deal of evidence from Nepal, sharing an open border with Bihar, suggests that women with migrant husbands were less likely to use contraceptives and access FP services though they had greater autonomy than those with resident husbands [9][10][11][12]. Primary research conducted in Nepal also noted that women with migrant husbands were less likely to discuss FP issues with their spouses [10,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The 2011 census revealed that one in every four households (25.4%; 1.38 million households) had at least one absent or migrant member, making internal migration rate of 18% from rural to urban areas and 3.8 million Nepalese obtained international work permits in 2014/2015 fiscal year (S. Ghimire et al, 2018). However, Mehata et al (2020) mention that about a third of the households (30%) had a least one member of the family migrated and the proportion of migration is higher in the rural and disadvantaged regions of Nepal. Employment is the main reason for migration (70%), with remittances from international migrants the primary income source for many households (Thapa et al, 2020).…”
Section: Situation Of Migration In Nepalmentioning
confidence: 99%
“…The literature on migration and health presents the complex relationship of migration on health and fertility. Spousal separation is more common among married women of reproductive age in rural areas (37%) than their urban counterparts (32%) (Mehata et al, 2020). Shattuck et al (2019) describe that there are health disparities among women with migrant husbands, and negative consequences of migration on the health of other family members including mental health issues such as the feeling of loneliness, isolation depression, and higher levels of reproductive morbidity, sexually transmitted infections than women married to nonmigrants.…”
Section: Effect Of Migration On Reproductive Health and Marital Relationshipmentioning
confidence: 99%